A mono-center study on pathological types and 15-year epidemiology evolution of primary glomerular diseases - TIAN Kun; DUAN Li-ping; LI Yun; ZHENG Zhao-xia; HU Tian-xiao (Linchuang shenzangbing zazhi)
Objective To investigate pathological types and the evolutional features of epidemiology of primary glomerular disease in adult patients with renal biopsy in Handan, Hebei, China. Methods From April 2002 to April 2017, a total of 1627 adult patients with primary glomerular diseases in Department of Nephrology of Han Dan Municipal Central Hospital were selected. The pathological types of adult primary glomerular disease and the 15-year epidemiological evolution in Handan were retrospectively analyzed. Results Among 1 627 adult patients with primary glomerular disease in Handan, 876 patients were male( 53.84%) and 751 ones were female(46.16%), with the ratio of males to females of 1.17∶1, and the mean age of 40.1±15.8(18～79 years). Primary glomerular diseases were predominant in adolescent and youths(18～40 years, 51.69%), with high incidence in males(53.84%). Membranous nephropathy(MN) was the most common pathological type, accounting for 46.28%, followed by minimal pathological changes(19.18%) and IgA nephropathy(IgAN)(17.33%). In recent years, the constituent ratio of membranous nephropathy which often occurs in the middle aged increased significantly(from 23.98% up to 55.84%).IgA nephropathy and minimal pathological changes had high incidence in young males,,and their constituent ratio was however lower than before(from 27.46% to 12.99% and 22.75% to 17.65%, respectively). The most common clinical syndrome was nephrotic syndrome(64.84%) and chronic nephritis syndrome(24.65%); the most common nephropathy syndrome was membranous nephropathy(54.22%) and minimal glomerular pathological changes(26.87%); and the most chronic nephritis was IgA nephropathy(37%) and membranous nephropathy(36.75%). Conclusions Primary glomerular diseases were more common in male young persons in Handan. Membranous nephropathy is the most common pathological type, and its constituent ratio exhibits an ascending trend; minimal pathological changes and IgA nephropathy are common; and the most common clinical manifestation is nephropathy syndrome.